2022
DOI: 10.21203/rs.3.rs-2316874/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repeatability of scheimpflug based corneal tomography parameters in advanced keratoconus with thin corneas

Abstract: Objective To determine the repeatability limits of corneal tomography parameters in patients with advanced and moderately thin keratoconic corneas to assist in planning thickness-based procedural interventions. Methods Prospective, single-centre, repeatability study. Three tomography scans using the Pentacam AXL were obtained from patients with keratoconus with thinnest corneal thickness TCT ≦ 400 µm (sub-400 group) and compared to those with TCT = 450–500 µm (450-plus group). Eyes with previous crosslinking… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although the eyes included in this study had a spectrum of keratoconus severity, measurements have been shown to have greater fluctuation with increasing severity. 21 In addition, some subjects may not have been out of contact lenses long enough before the scan, so the effect of contact lens use on the measured parameters must be taken into account, and thus, this study's findings may not apply to other groups of patients.…”
Section: Discussionmentioning
confidence: 94%
“…Although the eyes included in this study had a spectrum of keratoconus severity, measurements have been shown to have greater fluctuation with increasing severity. 21 In addition, some subjects may not have been out of contact lenses long enough before the scan, so the effect of contact lens use on the measured parameters must be taken into account, and thus, this study's findings may not apply to other groups of patients.…”
Section: Discussionmentioning
confidence: 94%
“…It is also known that the repeatability of corneal tomography measurements is significantly reduced in patients with advanced keratoconus and corneas thinner than 400 mm when compared with individuals with corneas thicker than 450 mm. 23 Moreover, the variability of measurements can be an indicator of clinical progression of keratoconus. 24 The present investigation showed a relatively large difference between the devices in corneal thickness measurements; for Revo, the values were significantly lower than for Pentacam AXL (535.54632.45 vs. 550.74631.55 mm), and this difference was even greater for thinnest pachymetry.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the repeatability of corneal tomography measurements is significantly reduced in patients with advanced keratoconus and corneas thinner than 400 μm when compared with individuals with corneas thicker than 450 μm. 23 Moreover, the variability of measurements can be an indicator of clinical progression of keratoconus. 24…”
Section: Discussionmentioning
confidence: 99%
“…The difference in measurements between different devices were statistically significant, and therefore should not be used interchangeably. Additionally, the repeatability may be affected according to the status of the measured cornea (i.e., healthy corneas, KC severity, thin corneas) [34].…”
Section: Elevation-based Corneal Tomographymentioning
confidence: 99%